Quantification of Plasmodium falciparum: validation of quantitative polymerase chain reaction assays for detection of parasites in controlled human malaria infection studies - Kibwana, Elizabeth; Kimani, Domtila; Edwards, Nick J.; Keter, Kelvias; Mutiso, Agnes; Nyamako, Lydia; Gatheru, Rose; Hill, Adrian V. S.; Bejon, Philip; Ewer, Katie J.; Kapulu, Melissa C. (Frontiers in Malaria, 2025)
BackgroundControlled human malaria infection (CHMI) studies are considered a powerful tool for assessing the efficacy of malaria vaccines and investigating immunity against infection. The monitoring of infection has historically been carried out by microscopy and/or more recently sensitive quantitative polymerase chain reaction (qPCR) based on the 18S ribosomal RNA (rRNA) gene. Here we describe the validation of a molecular assay previously developed to quantify malaria parasites in CHMI.MethodsWe used primers and probes for the 18S rRNA Plasmodium falciparum gene. The validation of the assay was performed using cultured 3D7 parasites to generate standards of known quantities of parasites. We determined the specificity, accuracy, precision, lower limit of detection, linearity, and robustness. We also evaluated the effect of using different volumes of whole blood for DNA extraction on the assay performance.ResultsThe validation revealed: (1) specificity of 100% (n=5 independent experiments); (2) linearity with R2 values ≥ 0.98, a slope of −3.8 to −3.1, and efficiency 89–100%; (3) lower limit of detection of 0.3 parasites/microliter and lower limit of quantification of 2.6 parasites/microliter; (4) precision with both inter-assay repeatability and intra-assay reproducibility with coefficients of variation (CV) values of <10%; and (5) accuracy and good extraction efficiency of >90%. The use of large blood volumes for extraction had an adverse effect on precision.ConclusionWe show that this qPCR method for P. falciparum parasite quantification from whole blood is specific, precise, sensitive, accurate, and robust. However, our whole blood qPCR method is not suitable when DNA extraction is from large blood volumes, where using a larger extraction volume of 1000 µl has a considerable effect on the robustness, reproducibility, and repeatability of qPCR, highlighting the importance of standardized protocols in DNA extraction. Other qPCR methods should be considered where high volumes of blood are required.